THE INFLUENCE OF CEO POWER ON COMPANY PERFORMANCE WITH GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE - Susilawati, Made; Dewa, Saroja Sari; Utami, Eva Yuniarti; Maulana, Yasir; Iman, Nurul (ITB AAS Indonesia Surakarta, 2024)
Abstract This research is quantitative research with an explanatory approach, namely an approach that uses several previous studies as the main focus in exploring in more depth the research being carried out. The data used in this research is primary data that researchers distributed to Wulling leaders and employees spread throughout Indonesia. The data distributed using an online questionnaire instrument contains 4 statements out of 16 statements on the dependent variable, 6 questions, the independent variable, 6 questions, and the moderate variable, 4 questions. The data must go through several stages first, starting with the validity test, reliability test and path coefficient. From the characteristics of the explanation that the researcher describes, it can be seen that the analysis tool used is smart PLS 4.0. Thereult show that the CEO Power variable has a positive relationship and has a significant influence on the Company Performance variable because superior policies, superior power, superior networks, and superior behavior can change everything to the point that it has an impact. on Company Performance. The results that the researcher concluded were caused by the P-Values which were positive and were below the 0.05 significance level, namely 0.017. Apart from that, the Good Corporate Governance variable can strengthen the influence of the CEO Power variable on company performance because good policies issued by the leadership are part of Good Corporate Governance and good governance is the result of good superior policies as well. This means that both Good Corporate Governance and CEO Power are two things that influence each other. The results that the researchers concluded were caused by the same thing because the P-Vlaues value was positive and was below the 0.05 significance level, namely 0.017. Thus, the first and second hypotheses in this research can be accepted and proven. Keywords: CEO Power, Good Corporate Governance, Company Performance